The Effect Of E-Service Quality and Brand Trust On Repurchase Intentions For Gloo Baby N Kids Products On E-Commerce Tiktok Shop - Mariana Rachmawati; Rini Handayani; Elena Maulidya Yuhananda (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This Research is to determined the effect of E-Service Quality and Brand Trust towards Repurchase Intentions for Gloo Baby n Kids Product on E-Commerce TikTok Shop. The object of this research is Gloo Baby n Kids Products at TikTok Shop E-Commerce with the consumer observation unit Gloo Baby n Kids at TikTok Shop E-Commerce. The research method in this study is a research descriptive verification. Multiple linear regression hypothesis test. Research on data collection techniques for field research, questionnaires, and library research. The number of samples is 99 respondents with non-probability sampling technique. The results showed that the E-Service Quality and Brand Trust variables had an effect on Repurchase Intention. The results of the study show that there is a positive influence of E-Service Quality and Brand Trust on Repurchase intentions.